Community of Practice group formation model based ontology / Faidah Muhammad - Muhammad, Faidah (2016)
Establishment of a Community of Practice (CoP) has been proposed to be an effective approach to enable knowledge sharing among practitioners. Community of Practice (CoP) has been identified as approaches to share tacit knowledge among practitioner. Previous research has addressed CoP formation issues related to common ground such as finding the similarity of interest, experienced and practice among the members of the community. These issues have contributed to the failure of CoP itself. Therefore, for the CoP formation to be effective, the formation needs to take into account members identity and formation criteria that can influence the effectiveness of the community as a knowledge sharing group in practitioner environment. Hence, there are limited studies of group formation based on the practitioner criteria of CoP formation. Therefore, the main objective of this research is to identify the group formation criteria based knowledge sharing behaviour and to proposed a CoP group formation model based on the criteria of CoP group formation. Previous research has been using ontology in group formation to express semantic meaning of members' identification and group formation criteria. This approach has made a significant positive result to the group formation process using ontology. In this regard, the next objective of this research is to design and develop group formation domain ontology. In addition, other objective of this study is to evaluate the CoP group formation model to ensure the proposed model meets the requirement of practitioner environment. This study has been done based on a case study in large IT department. In order to identify group formation criteria, knowledge sharing behaviour among practitioner was examined using a mixed method. The first phase investigated knowledge sharing behaviour through observation study. Based on the first phase, the findings were generalized using Social Network Analysis (SNA). The findings are categorized into three criteria; ability, job context and relation. This research has proposed CoP group formation model and Group Formation Domain Ontology. The proposed models are capable to assist organization to formed CoP especially in practitioner setting.